A Golgi UDP-GlcNAc transporter delivers substrates for N-linked glycans and sphingolipids. (October 2018) - Ebert, Berit; Rautengarten, Carsten; McFarlane, Heather; Rupasinghe, Thusitha; Zeng, Wei; Ford, Kristina; Scheller, Henrik; Bacic, Antony; Roessner, Ute; Persson, Staffan; Heazlewood, Joshua
Abstract Glycosylation requires activated glycosyl donors in the form of nucleotide sugars to drive processes such as post-translational protein modifications and glycolipid and polysaccharide biosynthesis. Most of these reactions occur in the Golgi, requiring cytosolic-derived nucleotide sugars, which need to be actively transferred into the Golgi lumen by nucleotide sugar transporters. We identified a Golgi-localized nucleotide sugar transporter fromArabidopsis thaliana with affinity for UDP-N -acetyl-d -glucosamine (UDP-GlcNAc) and assigned it UDP-GlcNAc transporter 1 (UGNT1). Profiles ofN -glycopeptides revealed that plants carrying theugnt1 loss-of-function allele are virtually devoid of complex and hybridN -glycans. Instead, theN -glycopeptide population from these alleles exhibited high-mannose structures, representing structures prior to the addition of the first GlcNAc in the Golgi. Concomitantly, sphingolipid profiling revealed that the biosynthesis of GlcNAc-containing glycosyl inositol phosphorylceramides (GIPCs) is also reliant on this transporter. By contrast, plants carrying the loss-of-function alleles affecting ROCK1, which has been reported to transport UDP-GlcNAc and UDP-N -acetylgalactosamine, exhibit no changes inN -glycan or GIPC profiles. Our findings reveal that plants contain a single UDP-GlcNAc transporter that delivers an essential substrate for the maturation ofN -glycans and the GIPC class of sphingolipids. N -linked glycosylation is processed in the endoplasmic reticulum and Golgi for eukaryotic proteins. Now, a single Golgi-localized UDP-N -acetyl-d -glucosamine transporter was identified to be essential for the processing of proteinN -glycosylation and the synthesis of GlcNAc-containing sphingolipids.